2019
DOI: 10.1088/2515-7620/ab178a
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of tropical vegetation greenness using sea surface temperatures*

Abstract: Much research has examined the sensitivity of tropical terrestrial ecosystems to various environmental drivers. The predictability of tropical vegetation greenness based on sea surface temperatures (SSTs), however, has not been well explored. This study employed fine spatial resolution remotely-sensed Enhanced Vegetation Index (EVI) and SST indices from tropical ocean basins to investigate the predictability of tropical vegetation greenness in response to SSTs and established empirical models with optimal para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…SST has a crucial role in regulating terrestrial climate as an influential external factor [44], thereby controlling the spatiotemporal distribution of climate factors that, through physiological processes, have a direct impact on drought conditions, e.g., precipitation, temperature, soil moisture, and photosynthetic activity of vegetation [45]. By altering land surface temperature and precipitation, the West Pacific Warm Pool has a strong but erratic impact on net ecosystem productivity in both the northern (negative correlation) and southern (positive correlation) hemispheres [46].…”
Section: Of 20mentioning
confidence: 99%
See 1 more Smart Citation
“…SST has a crucial role in regulating terrestrial climate as an influential external factor [44], thereby controlling the spatiotemporal distribution of climate factors that, through physiological processes, have a direct impact on drought conditions, e.g., precipitation, temperature, soil moisture, and photosynthetic activity of vegetation [45]. By altering land surface temperature and precipitation, the West Pacific Warm Pool has a strong but erratic impact on net ecosystem productivity in both the northern (negative correlation) and southern (positive correlation) hemispheres [46].…”
Section: Of 20mentioning
confidence: 99%
“…As a result of the time lag between each link in this cause-and-effect chain, SST indices are more predictive of terrestrial photosynthesis variability than meteorological factors [56]. Several studies have shown that plant greenness in the dry and semi-arid climatic zones of the tropical belt may be predicted three to six months ahead of time using SST [45].…”
Section: Of 20mentioning
confidence: 99%